Landslides detection and volume estimation in Jinbu area of Korea - Cha, Dusong; Hwang, Jinseong; Choi, Byoungkoo (Forest science and technology, 2018)
Shallow landslides triggered by heavy rainfall are common phenomena in mountainous areas of temperate monsoon regions. On July 2006 intensive shallow landslides occurred in Jinbu area, Korea triggered by heavy rainfall. An inventory of 1412 shallow landslides was constructed from intensive field works and interpretation of web-based aerial photographs, and all landslides detected were mapped across the study area. The measurements were geometrical properties (landslide length, landslide width, landslide depth) of individual landslides to establish the relationship linking landslide area to landslide volume. The relationship linking landslide area to landslide volume was obtained from the inventory of 930 landslides and is a power law function with a scaling exponent γ = 1.02, covers four orders of magnitude of landslide area and landslide volume, and is in reasonable agreement with existing relationships obtained from small scale shallow landslide events. The relationship can be used to estimate the volume of individual landslides with shallow soil depth when the area of landslide is known. However, geological and geomorphological setting should be considered to calculate accurate landslide volume with respect to disaster prevention.